Concept Mapping as a Clinical Learning Strategy on the Competency Scores of Nursing Students (Indian Journal of Public Health Research & Development, 2020)
Background: Nursing students are valuable human resources. Therefore, its crucial to detect potentialclinical difficulties experienced by the nursing students and identify appropriate ways to enhance theirlearning as well as academic and clinical outcome.Objective:1. To determine the effect of concept mapping on the clinical competency scores of nursing students.2. To compare the clinical competency scores of the subjects during the first few weeks of training inconcept mappingMethod: Quasi experimental research study with Posttest only design was used to accomplish the purposeof the study. The study setting comprised of two private nursing colleges offering diploma, degree andPG program in nursing. Data was collected from the II and III B.Sc. Nursing students in both the college.Convenient sampling was used in the study. The study sample consisted of 136 student nurses. The datacollection tool comprised of assessment of 1) Baseline Performa of the students and 2) Concept map clinicalgrading rubric to evaluate the concept mapsResult: Based on the findings of the study there was a significant improvement in the competency of conceptmap preparation. This was evidenced by the increase in competency scores from week one to week two andthree.Conclusion: The technique was beneficial for the students as well as educators who had noticed change inthe performance of the students who practiced the concept mapping technique. It also enhanced the studentsto prioritize the need and the care to be provided to the patient.
Keywords: Concept mapping, clinical learning strategy, competency, nursing students.